2019
DOI: 10.1101/607374
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An analytical theory of balanced cellular growth

Abstract: The biological fitness of unicellular organisms is largely determined by their balanced growth rate, i.e., by the rate with which they replicate their biomass composition. Natural selection on this growth rate occurred under a set of physicochemical constraints, including mass conservation, reaction kinetics, and limits on dry mass per volume; mathematical models that maximize the balanced growth rate while accounting explicitly for these constraints are inevitably nonlinear and have been restricted to small, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 55 publications
(67 reference statements)
1
40
0
Order By: Relevance
“…Overall, the largest deviations between observed concentrations and predictions are seen in the two non-minimal conditions, which also exhibit the fastest growth (µ > 1 h −1 ). A recent analytical study of balanced cellular growth indicates that these deviations may result from the influence of an increased growth-related dilution of cofactors and other intermediate metabolites, a phenomenon not included in our simulations 12 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, the largest deviations between observed concentrations and predictions are seen in the two non-minimal conditions, which also exhibit the fastest growth (µ > 1 h −1 ). A recent analytical study of balanced cellular growth indicates that these deviations may result from the influence of an increased growth-related dilution of cofactors and other intermediate metabolites, a phenomenon not included in our simulations 12 .…”
Section: Resultsmentioning
confidence: 99%
“…In principle, these questions would best be addressed in the context of a whole-cell model of balanced growth that combines mechanistic descriptions of metabolism and protein production. However, while such models have been described conceptually 11,12 , kinetic parameterizations are unavailable for a majority of the relevant enzymatic reactions 13 , preventing a truly mechanistic description that combines metabolism and protein translation. Thus, we here focus on protein production alone, taking the experimentally observed output of translation (proteome production rate and composition in a given growth condition), the corresponding input (charged tRNAs), and the kinetics of individual translation reactions as given.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Crowding, in turn, impacts processes comprising macromolecular diffusion (7,8), bacterial nucleoid organization (9), and protein-DNA interactions (10). Accordingly, it was suggested that biomass growth rate depends on dry-mass density and crowding (11)(12)(13)). Yet, the connection of cell-volume growth, biomass growth, and to the crowded state of the cytoplasm remain largely unknown (5).…”
mentioning
confidence: 99%
“…rRNA forms the central part of the catalyst of peptide elongation, while tRNA forms the core of the substrate; together, they account for the bulk of cellular RNA [2]. Their cytosolic concentrations at different growth rates in E. coli are well described by an optimality assumption [9,36,37]. Moreover, chromosomal gene positions in E. coli are known to affect the expression of both tRNA and rRNA genes [38,39]; both types of genes are located closer to oriC in fast compared to slowly growing bacteria, with rRNA genes positioned closer to oriC than tRNA genes in most examined fast-growing bacteria [27].…”
Section: Introductionmentioning
confidence: 99%